Pengamanan Restful API menggunakan JWT untuk Aplikasi Sales Order - Edy Edy; Ferdiansyah Ferdiansyah; Wahyu Pramusinto; Sejati Waluyo (Ikatan Ahli Informatika Indonesia (IAII), 2019)
The company has an important role in attracting the attention of customers by promoting its products and services so that it can be widely known by the community through the sales division (sales person). The biggest challenge faced by companies is related to marketing, namely stable and sustainable income growth, and customer loyalty. So that the application of information and communication technology is needed in the business world as a tool to win the main competition in marketing products or services. In the company, order data made by the sales person is still via telephone. You need an application to speed up the product ordering process to customers. To solve these problems, each sales person will use a sales order application through a smartphone device that will make product orders. And product ordering data will go to a web-based application run by admin for the invoice creation process. This application is designed using the RESTful API which is one of the implementation models of the web service and. In terms of data exchange security using the Json Web Token. With this sales order application, it can simplify the sales person's performance in marketing their products. This application work runs well on the web and android device so the process of ordering products becomes easier. The use or json web token authentification on the RESTful API makes the application more secure because this application can not be accessed if it does not use tokens.